(untitled) (Heritage, 2023)
In contrast to the satirical grotesque in the story collection Utuljena kandila, the grotesque in Dragiša Vasić’s story collection Vitlo appears with richer, more complex meanings and effects, including the funny and the uncanny. The story "Vitlo" contains a series of typical grotesque motifs (graveyard, night, disease, the excessive bodily aspects) and mechanisms (sudden re-signification involving relations of the known/unknown, idyllic/terrifying) that participate in the construction of the dominant twilight atmosphere. In the story "Vitlo", the narrator, however, does not delve into the mysteries of death, as it might seem after the first story fragment, but into the terrifying secrets of life. An aspect of vagueness or incomprehensibility colors the narrator’s memories of an event from his childhood – riding a yard winch. In our interpretation, the moment of the forced ride on the winch turns out to be a moment of insight into the essential abandonment and alienation of the narrative subject, while the cross-eyed view from the moving winch reveals the strangeness of the previously intimately experienced world. The mentioned memory, therefore, introduces the grotesque as understood by Wolfgang Kaiser - as a special structure of reality - into Vasić’s story. Although in the last fragment the narrator retreats from the most radical knowledge about the mentioned, grotesque structure of reality, and ends the narration with pantheistic worship of nature, this change of tonality remains in an unresolvable tension with the previous fragments.